2018
DOI: 10.1111/1346-8138.14741
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of patients with drug‐induced pemphigoid using the Japanese Adverse Drug Event Report database

Abstract: To clarify the incidence of drug‐induced pemphigoid in Japan, we conducted a database search and analysis using the Japanese Adverse Drug Event Report database (JADER). Among the cases recorded in JADER between April 2004 and November 2017, we targeted “pemphigoid” and analyzed the patients’ backgrounds, drug involvement, time of pemphigoid onset, outcomes and year reported. For cases where three or more drugs were reportedly involved, the signal index was calculated using the reporting odds ratio (ROR) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
(47 reference statements)
0
13
0
Order By: Relevance
“…An association between DPP4 inhibitors and pemphigoid has been reported [36,37]. As a consequence, the package inserts for DPP4 inhibitors, including teneligliptin, were revised to include a precaution regarding pemphigoid in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…An association between DPP4 inhibitors and pemphigoid has been reported [36,37]. As a consequence, the package inserts for DPP4 inhibitors, including teneligliptin, were revised to include a precaution regarding pemphigoid in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Adapted from Ohnuma et al 2 and anagliptin (111.07), which are less frequently used, 43,45,56 and omarigliptin (OR, 557.20), teneligliptin (OR, 29.23-161.9), and trelagliptin (OR, 178.18), which are available in fewer countries, such as Japan, Argentina, Korea, and India. 42,45,57 Whilst individual studies found no significant risk associated with sitagliptin use, a recent meta-analysis of randomized controlled trials involving sitagliptin, saxagliptin and linagliptin identified a significant association (OR, 7.38) 12,46,47 In addition to BP, DPP4i appear to predispose towards mucous membrane pemphigoid (MMP) development. In a study examining gliptin accountability in a cohort of 313 MMP patients, 17 of 24 gliptin-treated diabetic MMP patients were considered gliptin-induced MMP due to onset within <12 weeks.…”
Section: Bullous Pemphi G Oid and Mucous Memb R Ane Pemphigoidmentioning
confidence: 99%
“…The average latency period from the exposure of DPP4i use to BP diagnosis/clinical presentation ranges from 8 months to 2.25 years with even greater interpatient variability. 44,53,56,57,59,60 Since the concomitant use of metformin or other anti-hyperglycaemic agents is noted during the latency period, it was once speculated to play a role in the development of DPP4i-induced BP 45,51,[61][62][63] ; however, subsequent studies found the risk to be limited just to DPP4 inhibition. 49,53,55,64 Pooled analyses reveal that the risk of DPP4i is higher amongst males (OR, 1.91-5.31), 44,47,49,50 and the elderly (OR, 5.31).…”
Section: Bullous Pemphi G Oid and Mucous Memb R Ane Pemphigoidmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of ADRs of skin and subcutaneous tissue disorders was 0.41% in this surveillance. Pemphigoid was added to the package insert for teneligliptin during the observation period [23], having emerged as a possible ADR associated with DPP4 inhibitors, including teneligliptin [39][40][41][42]. In this surveillance, pemphigoid was reported as an ADR in five patients (0.05%).…”
Section: Safety In Overall Populationmentioning
confidence: 99%